A Hexasaccharide Containing Rare 2‐O‐Sulfate‐Glucuronic Acid Residues Selectively Activates Heparin Cofactor II. Issue 9 (26th January 2017) - Sankarayanarayanan, Nehru Viji; Strebel, Tamara R.; Boothello, Rio S.; Sheerin, Kevin; Raghuraman, Arjun; Sallas, Florence; Mosier, Philip D.; Watermeyer, Nicholas D.; Oscarson, Stefan; Desai, Umesh R.
Abstract: Glycosaminoglycan (GAG) sequences that selectively target heparin cofactor II (HCII), a key serpin present in human plasma, remain unknown. Using a computational strategy on a library of 46 656 heparan sulfate hexasaccharides we identified a rare sequence consisting of consecutive glucuronic acid 2‐ O ‐sulfate residues as selectively targeting HCII. This and four other unique hexasaccharides were chemically synthesized. The designed sequence was found to activate HCII ca. 250‐fold, while leaving aside antithrombin, a closely related serpin, essentially unactivated. This group of rare designed hexasaccharides will help understand HCII function. More importantly, our results show for the first time that rigorous use of computational techniques can lead to discovery of unique GAG sequences that can selectively target GAG‐binding protein(s), which may lead to chemical biology or drug discovery tools. Abstract : A computational strategy was used to identify a rare sequence of glucuronic acid 2‐ O ‐sulfate residues in a library of heparan sulfate hexasaccharides. The designed sequence was found to activate heparin cofactor II 250‐fold, while leaving antithrombin, a closely related serpin, essentially unactivated.